Влияние экспериментального гестационного диабета на уровень экспрессии мРНК Aire и характер дифференцировки Foxp3+ клеток в брыжеечных лимфоузлах у потомства - Камышный, А. М.; Прозорова, Т. М.; Камышная, В. А.; Kamyshny, A. M.; Prozorova, T. M.; Kamyshna, V. A.; Камишний, Олександр Михайлович; Прозорова, Тетяна Михайлівна; Камишна, Вiта Анатолiївна (My University, 2015)
Formation of immunological tolerance to self-antigens is an important mechanism that prevents development of the autoimmune diseases. Objective. With the help of molecular genetic and immunofluorescence techniques to investigate the effects of experimental gestational diabetes on the level of mRNA expression of autoimmune regulator Aire and differentiation features of Foxp3+ cells in mesenteric lymph nodes in the offspring of Wistar rats. Methods. To determine the level of Аire mRNA RT-PCR was performed in real-time by thermocycler CFX96™ Real-Time PCR Detection Systems («Bio-RadLaboratories, Inc», USA). The relative level of gene expression were studied with rat reference genes GAPDH by the method ΔΔCt. Statistical analysis were conducted using available software «Bio-Rad СFX Manager 3.1» (Bio-Rad, USA). The immunopositive Foxp3+-lymphocytes were determined using an indirect immunofluorescence technique with using a monoclonal rat antibody. Results. The offspring of experimental gestational diabetes rats showed the reduction of autoimmune regulator Aire mRNA in 2,3-8,1 times (p <0,05) in mesenteric lymph node cells compared to control animals. The observed decrease in the transcriptional activity of Aire is accompanied by reduction in the number of regulatory Foxp3+ lymphocytes in mesenteric lymph node in the offspring of rats with experimental gestational diabetes, as well as reduction of concentration of the transcription factor Foxp3 in lymphocytes of cortical plateau. Conclusion. The revealed changes evidence the abuse of formation of peripheral immunological tolerance and can trigger the development of autoimmune disease in the offspring of mothers with experimental gestational diabetes. За допомогою молекулярно-генетичних та імунофлюоресцентних методів досліджували вплив гестаційного діабету на рівень експресії мРНК автоімунного регулятора Аire та характер диференціювання Foxp3+-клітин в брижових лімфатичних вузлах у нащадків щурів лінії Wistar. У нащадків щурів з експериментальним гестаційним діабетом виявлено зниження вмісту в клітинах брижових лімфатичних вузлів мРНК автоімунного регулятора Aire в 2,3-8,1 рази (p<0,05) порівняно з контрольною групою тварин. Виявлене зниження транскрипційної активності Aire супроводжується зменшенням кількості регуляторних Foxp3+-лімфоцитів в брижових лімфатичних вузлах у нащадків щурів з експериментальним гестаційним діабетом, а також зниженням концентрації транскрипційного фактору Foxp3 в лімфоцитах коркового плато. Виявлені зміни свідчать про порушення формування периферичної імунологічної толерантності та можуть бути тригером розвитку аутоімунних захворювань у нащадків від матерів з експериментальним гестаційним діабетом.
The influence of experimental gestational diabetes on expression of Aire mRNA and character of differentiation of Foxp3+ - cells in mesenteric lymph nodes in the offspring
Вплив експериментального гестаційного діа- бету на рівень експресії мРНК Аire та характер диференціювання Foxp3+- клітин в брижових лім- фатичних вузлах у нащадків
Keywords: experimental gestational diabetes; mesenteric lymph nodes; Aire; Treg; експериментальний гестаційний діабет; брижові лимфатичні вузли